Book Review: In This Together: Fifteen Stories of Truth and Reconciliation. - Belczewski, Andrea Robin (Journal of the Canadian Association for Curriculum Studies, 2017)
Numerous atrocities against Canada’s Indigenous peoples have revealed by the Truth and Reconciliation Commission (TRC) process. Truth is being told. But, how is reconciliation to be fostered? In her book entitled In This Together: Fifteen Stories of Truth and Reconciliation, Danielle Metcalfe-Chenail has gathered stories from a variety of individual Indigenous and non-Indigenous perspectives that tell the truth and offer means for reconciliation. Stories have been mechanisms for sharing wisdom since time immemorial – this book is no exception. Through the personal nature of these stories, we journey with each author through their unique adventures, circumstances, reflections, questions, and growth. In doing so, we are called to examine our own stories and embark on our own journey of truth and reconciliation—together.